ChemInform Abstract: Recent Advances in Radical Fluorination. Issue 44 (15th October 2015) - Chatalova‐Sazepin, Claire; Hemelaere, Remy; Paquin, Jean‐Francois; Sammis, Glenn M.
Abstract Review: [81 refs.